Improvement of the Detection Sensitivity for Tunable Diode Laser Absorption Spectroscopy: A Review - Lin, Shan; Chang, Jun; Sun, Jiachen; Xu, Peng (Frontiers in Physics, 2022)
Tunable Diode Laser Absorption Spectroscopy (TDLAS), a trace gas sensing technology based on infrared absorption spectroscopy, has been developed rapidly in the past few decades. The advantages of low cost and easy miniaturization could be applied in real-time monitoring. As an important factor, the detection sensitivity of TDLAS has been improved by a variety of methods. In this review paper, the important advances in TDLAS detection sensitivity are discussed, including the selection of absorption lines, the improvement of diode lasers, the design of effective optical paths, data demodulation, and the suppression of background interference. For gases with high application values, such as CH4, CO2, and NO, we summarize the detection sensitivity that the existing TDLAS system has been achieved, combined with the above-improved process. However, considering the principle of infrared absorption, the increase in detection sensitivity could reach an ultra-limit. Therefore, the hypothesis of the sensitivity limit of TDLAS is proposed at the end of the paper, through the quantization analysis.